Improving productivity, fruits physical and chemical properties of mango trees “Keitt cv.” using ammonium nitrate, cobalt sulfate and vitamin B12 - Hassan, A. M.; Haggag, L. F.; Elhady, E. S. (International Journal of Agricultural Technology, 2024)
Mango is one of the best fruit crops in the world due to its delicious taste and flavor as well as its content of many nutrients, but the productivity of trees sometimes suffers from a deficiency in some areas and in some growing seasons. In this experiment, the effect of foliar spraying with some nutrients and compounds beneficial to trees conducted during the 2022 and 2023 seasons on a private orchard in Al Sharkia Governorate - Egypt. The results showed that foliar spraying with ammonium nitrate at 1% + cobalt sulfate at 100 ppm + vitamin B12 at 100 ppm together at three times during the growing season had the best significant effect on the amount of yield, physical properties of fruits, and most chemical properties of fruit juice, compared to trees that were treated the experimental materials individually